Proceedings. International Conference on Image Processing
DOI: 10.1109/icip.2002.1038156
|View full text |Cite
|
Sign up to set email alerts
|

Reliable and fast structure-oriented video noise estimation

Abstract: The purpose of this paper is to introduce a fast automated whitenoise estimation method which gives reliable estimates in images with smooth and textured areas. This method is a block-based method that takes image structure into account and uses a measure other than the variance to determine if a block is homogeneous. It uses no thresholds and automates the way that blockbased methods stop the averaging of block variances. The proposed method selects intensity-homogeneous blocks in an image by rejecting blocks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
117
0

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 7 publications
0
117
0
Order By: Relevance
“…In order to alleviate the overestimation of the amount of noise in [13], the proposed method in this paper presents new masks for homogeneity measurement and a more accurate threshold for the averaging process.…”
Section: Proposed Image Noise Variance Estimation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to alleviate the overestimation of the amount of noise in [13], the proposed method in this paper presents new masks for homogeneity measurement and a more accurate threshold for the averaging process.…”
Section: Proposed Image Noise Variance Estimation Methodsmentioning
confidence: 99%
“…In [13] the authors showed that the dividing pattern of 5 ×5 blocks is a good compromise between efficiency and effectiveness. Thus, the same dividing pattern is used in this paper.…”
Section: Homogeneity Measurementioning
confidence: 99%
See 3 more Smart Citations